Starting your own business - Fisher, Vicky; Video Education Australasia (Bendigo, Vic, : Video Education Australasia, 1993)
Interviews business consultants and dispels myths surrounding the glamour of starting your own business. Introduces three young people who have taken control of their own careers and reveals the planning process they have undertaken. This program is a valuable tool for students and prospective business operators
Title from title screen
Editor, Vicky Fisher ; camera, Rocco Fasano
DVD format
Keywords: New business enterprises; Small business; Entrepreneurship; Business planning